Damage analysis of retired typhoons in mainland China from 2009 to 2019 - Wan, Chengcheng; Yan, Yafei; Shen, Liucheng; Liu, Jianli; Lai, Xiaoxia; Qian, Wei; Nie, Juan; Wen, Jiahong (Natural hazards (Dordrecht), 2023)
Typhoon catastrophes can seriously threaten national and regional security and development. How to quantitatively portray the spatiotemporal characteristics and the causes of typhoon catastrophe losses will be an important subject of scientific research in terms of disaster risk reduction. In this study, the overall characteristics, spatial patterns, and main influencing factors of the losses caused by retired typhoons landing in mainland China from 2009 to 2019 were investigated, through the usage of improved typhoon disaster index ( G -index), spatial autocorrelation, and cold/hotspots analysis methods. The results showed that 18 retired typhoons affected 17 provinces in China from 2009 to 2019, among which the areas affected by minor, moderate, severe, and extremely severe disasters accounted for 38.02%, 44.16%, 13.84%, and 4.32%, respectively. The disaster has strong spatial clustering, and the hotspots based on the G index are the key areas to be concerned about prevention and mitigation against typhoon mega-disasters. Furthermore, the effects of exposed population, maximum wind speed, and maximum accumulative process precipitation on typhoon disaster losses were positively correlated, while the effects of exposed GDP (Gross Domestic Product) on disaster losses are weakly negatively correlated. This study identified the hotspots of typhoon catastrophes and underlined the efforts to formulate effective disaster risk reduction and build resilience.